An experimental study on the methods of quantifying fragmented flake. (April 2016) - Jayez, Mozhgan; Vahdati Nasab, Hamed
Abstract: Counting the chipped stones constitutes the foundation of any subsequent descriptive-interpretive study. The accurate counting methods of fragmented chipped stones are the integral part of lithic analysis. In this article we have discussed the classification of flake fragments and we have introduced different methods of counting fragmented flakes when refitting is impossible. Seven different assemblages of chipped stones have been experimentally fractured and their fragments have been counted by using different methods in order to find the best method in counting fragments in archaeological assemblages. Highlights: Use of improper counting procedures leads to under- or overestimation on the actual number of flakes. It is not accurate enough to simply count the number of broken segments and use them in the statistical analysis. The classification of segments presented so far is not comprehensive when dealing with highly segmented assemblages. Hiscock's procedure and average weight are suitable methods for counting the flakes in collections with extreme fractures.